Separate and Combined Mutagenic Effect of Gamma Rays and Nitroso Methyl Urea in Chickpea (Cicer arietinum) var. RSG- 963. - Meena Girraj Singh; Dwivedi Pratibha (International Journal of Life Sciences, 2016)
Comparative mutagenic effectiveness and efficiency of different dosage of gamma rays, NMU and their combined treatment were studied in the genotype of chickpea (Cicer arietinum) var. RSG – 963. Seeds of chickpea were treated with 5KR, 10KR and 15KR doses of gamma rays and 0.02% NMU independently and in combination. Gamma irradiation and NMU induced various chromosomal aberrations as scattered chromosomes, ring formation, stickiness at metaphase, formation of bridges, laggards, multi polarity at anaphase. It was revealed that the rate of cell division was affected and measured in term of mitotic index which decreased with the increase of doses of gamma rays. The combined treatment of physical and chemical mutagens was more effective in comparison to independent treatment. The higher doses of gamma rays and combined doses of gamma rays and NMU treatment revealed deleterious as there was less germination percentage observed in M1 generation.